In patient dermatology: characteristics of patients and admissions in Tribhuvan University (TU) Teaching Hospital - S Parajuli; U Paudel; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7936